Surface energy of ultrafine particles as a tool for creating nanomodifiers complexes - F. I. Rudnitsky; S. A. Kulikov; V. A. Shumigai (Литьë и металлургия, 2019)
The results of studies on the effect of particles of metal-abrasive sludge used as a potential modifier of gray cast iron are presented in the article.The influence of metal and non-metal components of the sludge is clarified and the prevailing influence of metal particles is established during the studies. The assumption is made about the mechanism of the effect of particulate additives from the viewpoint of self-organization phenomena in ultradispersed systems. The strength increase of cast iron CЧ20 as a result of the introduction of slurries into the melt reaches up to 25%.